МУЛЬТИМЕДИЙНЫЕ ТЕХНОЛОГИИ КАК ОСНОВА САМОСТОЯТЕЛЬНОГО ИЗУЧЕНИЯ ФОНЕТИКИ В СИСТЕМЕ «ПЕРЕВЁРНУТОГО КЛАССА» - Атдаева Тавус Какабаевна; Овезова Джумагозель Какамурадовна (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
The article examines the methodology of teaching practical phonetics of foreign languages based on the "Flipped Classroom" model. The author analyzes the possibilities of integrating multimedia resources into students' independent out-of-class work to optimize the educational process. Special attention is paid to the psychological aspects of learning, in particular, overcoming "pronunciation anxiety" and the distribution of cognitive load. A step-by-step algorithm for implementing inverted learning is proposed, along with a classification of digital tools that contribute to the effective formation of phonetic competence.